Facile synthesis of N vacancy g-C3N4 using Mg-induced defect on the amine groups for enhanced photocatalytic •OH generation - Lee, Youn Jun; Jeong, Yoo Jae; Cho, In Sun; Park, Seong Jik; Lee, Chang Gu; Alvarez, Pedro J.J. (Journal of Hazardous Materials, 2023)
Photocatalysis offers opportunities to degrade recalcitrant organic pollutants without adding treatment chemicals. Nitrogen (N) vacancy is an effective point-defect engineering strategy to mitigate electron-hole recombination and facilitate hydroxyl radical (•OH) production via superoxide radical (O2•-) generation during photocatalytic application of graphitic carbon nitride (g-C3N4). Here, we report a novel strategy for fabrication of N-vacancy-rich g-C3N4 (NvrCN) via post-solvothermal treatment of Mg-doped g-C3N4. The addition of the Mg precursor during the polycondensation of urea created abundant amine sites in the g-C3N4 framework, which facilitates formation of N vacancies during post-solvothermal treatment. Elemental analysis and electron paramagnetic resonance spectra confirmed a higher abundance of N vacancies in the resultant NvrCN. Further optical and electronic analyses revealed the beneficial role of N vacancies in light-harvesting capacity, electron-hole separation, and charge transfer. N vacancies also provide specific reaction centers for O2 molecules, promoting oxygen reduction reaction (ORR). Therefore, •OH generation increased via enhanced formation of H2O2 under visible light irradiation, and NvrCN photocatalytically degraded oxytetracycline 4-fold faster with degradation rate constant of 1.85 × 10−2 min−1 (light intensity = 1.03 mW/cm2, catalyst concentration = 0.6 g/L, oxytetracycline concentration = 20 mg/L) than pristine g-C3N4. Overall, this study provides a facile method for synthesizing N-vacancy-rich g-C3N4 and elucidates the role of the defect structure in enhancing the photocatalytic activity of g-C3N4.
Keywords: Amine groups; Antibiotic degradation; Facile synthesis; G-C3N4; Induced defects; N vacancy; Photo-catalytic; Reactive oxygen species; Recalcitrant organic pollutants; Solvothermal treatment; Antibiotic degradation; g-C3N4; N vacancy; Photocatalysis; Reactive oxygen species